Experimentally evolving Drosophila erecta populations may fail to establish an effective piRNA-based host defense against invading P-elements - Selvaraju, Divya; Wierzbicki, Filip; Kofler, Robert (Genome Research, 2024)
To prevent the spread of transposable elements (TEs), hosts have developed sophisticated defense mechanisms. In mammals and invertebrates, a major defense mechanism operates through PIWI-interacting RNAs (piRNAs). To investigate the establishment of the host defense, we introduced the P-element, one of the most widely studied eukaryotic transposons, into naive lines of Drosophila erecta. We monitored the invasion in three replicates for more than 50 generations by sequencing the genomic DNA (using short and long reads), the small RNAs, and the transcriptome at regular intervals. A piRNA-based host defense was rapidly established in two replicates (R1, R4) but not in a third (R2), in which P-element copy numbers kept increasing for over 50 generations. We found that the ping-pong cycle could not be activated in R2, although the ping-pong cycle is fully functional against other TEs. Furthermore, R2 had both insertions in piRNA clusters and siRNAs, suggesting that neither of them is sufficient to trigger the host defense. Our work shows that control of an invading TE requires activation of the ping-pong cycle and that this activation is a stochastic event that may fail in some populations, leading to a proliferation of TEs that ultimately threaten the integrity of the host genome.
10.1101/gr.278706.123